2007
DOI: 10.1063/1.2798868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate on the structure and orientation of ZnO thin film grown by rf-magnetron sputtering

Abstract: Effect of high-energy electron beam irradiation on the properties of ZnO thin films prepared by magnetron sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
4
22
1
Order By: Relevance
“…From this, we can determine the epitaxial relationship between a-plane ZnO and r-plane Al 2 O 3 as ð1 12 0ÞZnO==ð11 0 2Þ Al 2 O 3 and ½0 0 0 1ZnO==ð1 1 0 1Þ Al 2 O 3 , which was consistent to the relationship determined by RHEED and X-ray diffraction in our previous report [11]. Actually, this epitaxial relationship is frequently observed in the ZnO films grown on rplane sapphire substrates by metalorganic chemical vapor deposition (MOCVD) [24] or rf-magnetron sputtering [25] under the optimized growth conditions.…”
Section: Resultssupporting
confidence: 83%
“…From this, we can determine the epitaxial relationship between a-plane ZnO and r-plane Al 2 O 3 as ð1 12 0ÞZnO==ð11 0 2Þ Al 2 O 3 and ½0 0 0 1ZnO==ð1 1 0 1Þ Al 2 O 3 , which was consistent to the relationship determined by RHEED and X-ray diffraction in our previous report [11]. Actually, this epitaxial relationship is frequently observed in the ZnO films grown on rplane sapphire substrates by metalorganic chemical vapor deposition (MOCVD) [24] or rf-magnetron sputtering [25] under the optimized growth conditions.…”
Section: Resultssupporting
confidence: 83%
“…The effects of crystalline quality on the UV emission of ZnO films have been widely investigated, and some controversial results were reported [11][12][13][14]. Kim et al reported that the PL property of ZnO films was improved because the grain size increased with RF power, even if the crystallinity of the ZnO films was degraded due to an increase in the mosaicity of the films [14].…”
Section: Resultsmentioning
confidence: 97%
“…For example, Jeong et al found that the UV emission was dominating for the ZnO films deposited in pure O 2 ambient and the emission properties of the ZnO film are more dependent on the film stoichiometry than the film crystallinity [12]. It has also been reported that ZnO/GaAs (0 0 1) sample with pure texture structure and small grain sizes had the stronger UV emission than the single ZnO (0 0 0 2) crystal film on GaAs (1 1 1) substrate, indicating that the grain boundaries of the ZnO film play a minor role in UV emission [13]. On the other hand, Kim and coworkers reported that the optical properties of ZnO films were closely related to both grain size and crystallinity, and the ZnO film with the narrowest width of X-ray rocking curve and the lowest channeling minimum yield exhibited the narrowest UV emission peak [14].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Both O and Zn atoms exist on the growing surface of aplane ZnO. Therefore, native defects are energetically favorable and [20]. From Fig.…”
Section: Resultsmentioning
confidence: 92%